2013
DOI: 10.1007/s12471-012-0323-5
|View full text |Cite
|
Sign up to set email alerts
|

Detrimental effects of endogenous oestrogens on primary acute myocardial infarction among postmenopausal women

Abstract: Objective Traditionally, oestrogens were considered to be protective for the cardiovascular system for premenopausal women. Therefore, we conducted a retrospective case-control study to examine the association between endogenous oestrogens and acute myocardial infarction (AMI) risk among postmenopausal women. Methods A case-control study was performed among 30 primary AMI patients and 60 control subjects. Baseline characteristics data was collected and endogenous sex hormones levels were determined using chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 32 publications
0
15
1
Order By: Relevance
“…However, several studies have found no association between sex hormone levels and risk of death from CVD . We found a positive relationship between higher estradiol levels and risk of AMI in postmenopausal women . Exogenous hormones have been documented to increase risk of CVD in women and were not able to prevent recurrent myocardial infarction in postmenopausal women .…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…However, several studies have found no association between sex hormone levels and risk of death from CVD . We found a positive relationship between higher estradiol levels and risk of AMI in postmenopausal women . Exogenous hormones have been documented to increase risk of CVD in women and were not able to prevent recurrent myocardial infarction in postmenopausal women .…”
Section: Discussioncontrasting
confidence: 68%
“…Myocardial no‐reflow is defined as inadequate myocardial perfusion of a given coronary segment without angiographic evidence of mechanical vessel obstruction . We proved that endogenous estrogen was an independent risk factor of ST‐elevation myocardial infarction (STEMI) in postmenopausal women . We now examine the effects of endogenous estrogen on no‐reflow in postmenopausal women with STEMI.…”
Section: Introductionmentioning
confidence: 99%
“…Where we assumed that increased levels of female sex hormones were protective against the development of cardiovascular disease, our colleagues Mei Dong et al from Yantai, China suggest quite the opposite. In their paper published in this edition of the Netherlands Heart Journal the authors describe a relation between the occurrence of a myocardial infarction (MI) in post-menopausal women and levels of sex hormones [1]. They report that high levels of oestradiol and increased waist-to-hip ratio (WHR) are related to the occurrence of acute MI.…”
mentioning
confidence: 99%
“…In recent years many clinical trials have provided evidence that there are substantial gender differences in the pathophysiology, clinical presentation, diagnosis, and treatment of CAD [1][2][3][4][5]. Although women have a higher atherosclerotic burden, they are more symptomatic and have a lower prevalence of obstructive CAD than men [6][7][8][9][10].Whether these gender differences translate into different clinical outcomes in stable CAD has been unclear. While some reports found gender differences in outcomes for stable angina or acute coronary syndromes, others did not [11][12][13][14][15].…”
mentioning
confidence: 99%
“…In recent years many clinical trials have provided evidence that there are substantial gender differences in the pathophysiology, clinical presentation, diagnosis, and treatment of CAD [1][2][3][4][5]. Although women have a higher atherosclerotic burden, they are more symptomatic and have a lower prevalence of obstructive CAD than men [6][7][8][9][10].…”
mentioning
confidence: 99%